A computer system for production planning in clothing small enterprises and microenterprises - Ávila Gonzáles de Trinidad, María del Rocío (2021)
The computer system for production planning determines what and how much to produce in order to achieve the goals set by clothing small and medium enterprises (SMEs); that is, to meet the demands on time and get the maximum benefit. Using a quantitative approach, a mathematical programming model for goal optimization and the Scrum framework were implemented in the study. In addition, MS Excel software was used for both the mathematical model and databases. The interfaces for data entry and reporting solution were developed in the Java SE platform. The computer system was installed in two SMEs: It increased productivity in both of them and was accepted for its ease of use and quick adaptation. The pandemic did not allow the installation of the computer system in other SMEs.